2004
DOI: 10.17305/bjbms.2004.3367
|View full text |Cite
|
Sign up to set email alerts
|

Testing of analgesic effect of fluoxetine

Abstract: Fluoxetine is used in treatment of depression caused by a variety of different factors and from year to year new indications are being added, especially in conditions followed with strong bouts of pain. Additional fluoxetine based therapy that is known to help in improvement of mental state and mood stabilization can significantly increase analgesic effects. Analgesic effects of fluoxetine as well as of fluoxetine in combination with morphine were analyzed on albino mice of both genders. The sense of pain was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Antidepressant drugs are reported to be used as co-analgesics in clinical management of migraine and neuropathic pain [45], [46]. Several studies have reported that a selective serotonin reuptake inhibitor, fluoxetine, produces an antinociceptive effect in pain assays, including the hot plate test [47], [48]. In our experiments, DKO animals exhibited altered pain sensitivity to an acute thermal stimulus in the hot plate model supporting 5-HT involvement in the regulation of pain.…”
Section: Discussionsupporting
confidence: 76%
“…Antidepressant drugs are reported to be used as co-analgesics in clinical management of migraine and neuropathic pain [45], [46]. Several studies have reported that a selective serotonin reuptake inhibitor, fluoxetine, produces an antinociceptive effect in pain assays, including the hot plate test [47], [48]. In our experiments, DKO animals exhibited altered pain sensitivity to an acute thermal stimulus in the hot plate model supporting 5-HT involvement in the regulation of pain.…”
Section: Discussionsupporting
confidence: 76%
“…For example, citalopram produces antinociceptive effects in both rats [222-224] and mice [219,225]. Such antinociceptive behaviors were reported with other SSRIs such as fluoxetine [226,227], fluvoxamine [219,222,228], paroxetine and sertraline [229-232] (Table 3). Interestingly, the effects of fluoxetine are completely blunted in 5-HT depleted animals [227,233] suggesting that SSRIs-induced antinociception involves serotonergic pathways.…”
Section: Monoamines Reuptake Inhibitors and Pain Preclinical Outcomesmentioning
confidence: 80%
“…In addition, we reported here the existence of a direct correlation between despair behaviour and enhanced pain sensitivity (Figure 7(b)), indicating a higher sensitivity to the antidepressant treatment in sciatic-operated mice, in which an enhanced pain sensitivity was observed. Both acute and chronic fluoxetine treatment were reported to elicit antinociceptive effects (Begović et al, 2004; Singh et al, 2001) in addition to its antidepressant properties in a mouse model of anxiety/depression (David et al, 2009). Furthermore, recent evidence reveals that particular antidepressants attenuated the function of glutamate GluN receptors, suggesting that this mechanism contributes to their therapeutic effects in chronic pain (Micó et al, 2006; Sánchez-Blázquez et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rats with anxiety-like or despair behaviours, comorbid with chronic neuropathic pain, showed impaired noradrenergic neurotransmission (Alba- Delgado et al, 2013;Bravo et al, 2012Bravo et al, , 2014. Finally, inhibitors of serotonin uptake used as antidepressant compounds also elicit antinociceptive effects in animal models (Begović et al, 2004;Singh et al, 2001;Valverde et al, 1994), and combined serotonin and noradrenaline uptake inhibition conferred increased analgesic benefits (Maletic and Raison, 2009). Thence, we decided to analyse the existence of serotonergic neurotransmission alterations in the PFC related to neuropathic pain.…”
Section: Analytementioning
confidence: 99%